Gangsters vs. Nazis: how Jewish mobsters battled Nazis in wartime America - Benson, Michael (Citadel Press, 2022)
part 1. The cloven hoof: Jewish gangsters ; Rise of fascism ; Fritz Kuhn ; Nazi youth camps -- part 2. New York City: Judge Perlman and Meyer Lansky ; Murder, Inc. ; The list ; Yorkville ; White Plains -- part 3. Chicago: Father Coughlin, radio priest ; Herb Brin, fighter of fascists ; Sparky and Barney ; The Germania Club -- part 4. Newark: Longie Zwillman ; Nat Arno ; Arno's Army ; Schwabbenhalle ; Irvington ; Union City ; Return to the Schwabbenhalle -- part 5. Middle America: William Dudley Pelley ; Davey the Jew ; The Elks Lodge Beatdown ; The Great Lakes cities -- part 6. West Coast: The Hollywood war ; Mickey Cohen and Bugsy Siegel -- part 7. The Bund's last gasp: Garden party ; Pearl Harbor ; Nazi perverts and thieves.